Revival of philosophy of law in contemporary Ukraine - Bihun, V.S. (Інститут держави і права ім. В.М. Корецького НАН України, 2003)
В кратком англоязычном изложении отмечаются нынешние тенденции развития философии
права в современной Украине. Возрождение отечественных исследований в этой области связывается с знаменательным событием основания и выхода в свет данного журнала, который задуман не только как форум для заинтересованных философией права в Украине, но и с целью служить
ареной для международного философско-правового дискурса. This English language note presents a brief survey of the current tendencies in the development of
philosophy of law in the contemporary Ukraine. The revival of Ukrainian studies in this area is connected
with and marked by the celebrated establishment and publication of the present international
Journal, which is thought not only as a forum for those interested in the philosophy of law in Ukraine,
but also as a means for facilitation of the international discourse in philosophy of law.